2024
DOI: 10.1111/pim.13025
|View full text |Cite
|
Sign up to set email alerts
|

Complement receptor 3 is required for maximum in vitro trogocytic killing of the parasite Trichomonas vaginalis by human neutrophil‐like cells

Emma N. Trujillo,
Barbara A. Flores,
Isabel V. Romero
et al.

Abstract: Trichomonas vaginalis (Tv) is a parasite that causes trichomoniasis, a prevalent sexually‐transmitted infection. Neutrophils are found at the site of infection, and can rapidly kill the parasite in vitro, using trogocytosis. However, the specific molecular players in neutrophil killing of Tv are unknown. Here, we show that complement proteins play a role in Tv killing by human neutrophil‐like cells (NLCs). Using CRISPR/Cas9, we generated NLCs deficient in each of three complement receptors (CRs) known to be ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“… 66 Recently, another group demonstrated that complement receptor 3 is required for human neutrophil-like cells’ maximum in vitro trogocytic killing of T. vaginalis . 67 …”
mentioning
confidence: 99%
“… 66 Recently, another group demonstrated that complement receptor 3 is required for human neutrophil-like cells’ maximum in vitro trogocytic killing of T. vaginalis . 67 …”
mentioning
confidence: 99%